2020
DOI: 10.1186/s12885-020-6524-1
|View full text |Cite
|
Sign up to set email alerts
|

The combination of CTCs and CEA can help guide the management of patients with SPNs suspected of being lung cancer

Abstract: Objective: Solitary pulmonary nodules (SPNs) is a common radiographic finding and require further evaluation because of the possibility of lung cancer. This study aimed to determine the sensitivity and specificity of circulating tumour cells (CTCs) as a marker for the diagnosis of SPNs and the integration of CTCs, carcinoembryonic antigen (CEA) and imaging findings to improve the sensitivity and specificity of diagnosis in patients with SPNs suspected of being lung cancer. Method: For the serum biomarker assay… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
(28 reference statements)
1
16
1
Order By: Relevance
“…In this study, the results revealed that the combination of conventional CEA values with CTC counts (i.e., number of CD45 neg EpCAM pos CTCs or CD45 neg EpCAM neg cells) can significantly discriminate CRC’s advanced or metastatic status ( Figure 5 , Figure 6 and Figure 7 and Table 3 and Table 4 ). These findings are also similar to those of other studies [ 31 , 32 , 33 ]. First, Aggarwal et al observed that the performance of cancer prognosis among metastatic CRC patients can be distinguished by a combination of the CEA level and baseline CTC count with a cutoff point of 3/per 7.5 mL, suggesting that the performance of the CEA level could be improved by combining it with the CTC marker [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, the results revealed that the combination of conventional CEA values with CTC counts (i.e., number of CD45 neg EpCAM pos CTCs or CD45 neg EpCAM neg cells) can significantly discriminate CRC’s advanced or metastatic status ( Figure 5 , Figure 6 and Figure 7 and Table 3 and Table 4 ). These findings are also similar to those of other studies [ 31 , 32 , 33 ]. First, Aggarwal et al observed that the performance of cancer prognosis among metastatic CRC patients can be distinguished by a combination of the CEA level and baseline CTC count with a cutoff point of 3/per 7.5 mL, suggesting that the performance of the CEA level could be improved by combining it with the CTC marker [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…First, Aggarwal et al observed that the performance of cancer prognosis among metastatic CRC patients can be distinguished by a combination of the CEA level and baseline CTC count with a cutoff point of 3/per 7.5 mL, suggesting that the performance of the CEA level could be improved by combining it with the CTC marker [ 31 ]. Zheng et al noticed that the combination of the CTC count with the CEA level could be a tool with high diagnostic efficacy for early lung cancer diagnosis [ 32 ]. Shi et al proved that CTCs expressing MAGE3 (melanoma-associated antigen 3), survivin, and CEA were predictive of cryosurgery’s efficacy in unresectable hepatocellular carcinoma [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results show that there was little difference in the individual detection efficacy between these markers, and the AUC values were all less than 0.6, suggesting that they were not suitable as biomarkers for the diagnosis of lung cancer. In some studies, the CEA expression level was shown to have a certain application value in the determination of pulmonary nodule benignity and malignancy ( 11 , 33 , 34 ), while in this study, it was not shown to have an application value. This may be because serum CEA expression levels in patients with pulmonary nodules < 2 cm tend to be within a normal detection threshold range.…”
Section: Discussioncontrasting
confidence: 56%
“…The degree of serum CEA increase is related to the extent of cancer focus, and its dynamic changes can reflect the patient's response to treatment and prognosis. Patients with a progressive increase in the measured value tend to have a poor prognosis, while patients with firstly decreased and then increased values are mostly experiencing signs of tumor recurrence (Zheng et al, 2020). Glutathione-S-transferaseπ (GST-π) is significantly increased in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%